Elevated serum sialic acid in pregnancy. - Crook, M (1997)
OBJECTIVE: Serum sialic acid has recently gained interest as a possible cardiovascular risk factor as well as a potential tumour marker. The effect of pregnancy on serum sialic acid is unclear particularly in the post-partum period. DESIGN: Longitudinal cohort. SETTING: Teaching hospital antenatal clinic. POPULATION: 29 pregnant women, 27 age matched non-pregnant women. METHODS: Specific enzymatic assay for sialic acid. The first serum sample was taken between 37 and 42 weeks of gestation; in 22 women this was followed by a second serum sample at 12 weeks postpartum. Serum sialic acid concentration was also measured in the 27 controls. RESULTS: Mean (SD) serum sialic acid concentration was higher during pregnancy than post-partum: 91.1 (11.1) v 77.5 (11.1) mg/dl (p < 0.001); or in the control group: 66.0 (9.7) mg/dl (p < 0.001). CONCLUSIONS: Serum sialic acid is elevated during pregnancy and postpartum.